2015
DOI: 10.1093/geront/gnv096
|View full text |Cite
|
Sign up to set email alerts
|

Do Canes or Walkers Make Any Difference? NonUse and Fall Injuries

Abstract: Providers must place increased emphasis on the importance of cane/walker use for injury prevention through patient education to promote personal relevance, proper fitting, and training. New strategies are needed to improve device acceptability and accessibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…These findings identify that assistive device use might precipitate falling among home care clients with a neurological health condition, and these findings are relevant to the work of individuals tasked with coordinating home care and home health care practitioners to help prevent accidental falls among higher risk patient groups. The use of assistive devices for locomotion indoors, such as canes and walkers, by home care clients is typically a supportive measure to prevent falls, and previous studies have identified that falls occurred when clients were not using these assistive devices [39]. The use of canes and/or walkers may also be attributed to the fact that these users may be weaker than non-users, and so these users may be more susceptible to falls.…”
Section: Implications For Policies and Practices Pertaining To Home Carementioning
confidence: 99%
“…These findings identify that assistive device use might precipitate falling among home care clients with a neurological health condition, and these findings are relevant to the work of individuals tasked with coordinating home care and home health care practitioners to help prevent accidental falls among higher risk patient groups. The use of assistive devices for locomotion indoors, such as canes and walkers, by home care clients is typically a supportive measure to prevent falls, and previous studies have identified that falls occurred when clients were not using these assistive devices [39]. The use of canes and/or walkers may also be attributed to the fact that these users may be weaker than non-users, and so these users may be more susceptible to falls.…”
Section: Implications For Policies and Practices Pertaining To Home Carementioning
confidence: 99%
“…In the current study, we noticed a high proportion of patients from either group that were not using any devices. In a study on community-dwelling older adults with fall history, the most frequent reasons for nonuse of canes and devices included believing it was not needed, forgetfulness, the device making them feel old, and inaccessibility [ 34 ]. The same study found that nonuse led to a significantly higher risk of falls resulting in surgery than among device users [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on community-dwelling older adults with fall history, the most frequent reasons for nonuse of canes and devices included believing it was not needed, forgetfulness, the device making them feel old, and inaccessibility [ 34 ]. The same study found that nonuse led to a significantly higher risk of falls resulting in surgery than among device users [ 34 ]. The underlying reasons for underutilization of these devices in this population should be investigated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with Parkinson's disease, movement disorder can severely disrupt the performance of daily activities and increase the risk of falling. Despite various existing walkers are owned by seniors, reported statistics show that 33% of people over 60 years fell at least once (Luz et al, 2017). We argue that intelligence is essential for an elderly walker to detect abnormal user behaviors and provide timely safety support, since primitive assistance devices, such as rollators and walkers, are much likely to fail (Bertrand et al, 2017).…”
Section: Introductionmentioning
confidence: 91%